Linear correlations between feed intake and ingestive behavior of feedlot lambs - Figueiredo, Cibelle Borges; Santana Junior, Hermogenes Almeida; Oliveira, Aracele Prates; Santos, Maurílio Souza dos; Mendes, Fabrício Bacelar Lima; Cardoso-Santana, Elizângela Oliveira (Comunicata Scientiae, 2019)
The objective of this study was to evaluate linear correlations between feed intake and ingestive behavior of feedlot lambs. Were used ten castrated male Santa Inês sheep with a body weight of 20 ± 4.38 kg, at four months of age. The experiment lasted 50 days, with five 10-d periods, in which an evaluation of feed intake and ingestive behavior was undertaken per period, totaling 50 replicates. The diet was composed of concentrate ingredients only. The analyses were performed by Pearson’s linear correlations and the t test, and means were considered significant when P≤0.05. Intake showed positive correlations (P≤0.05) with the times spent feeding and ruminating and total chewing time, and a negative correlation (P≤0.05) with other activities. Positive correlations were found between the number of feeding periods, number of other activities and the time per rumination period with intake (P≤0.05). A negative correlation was found between the feed efficiency of dry matter and the intake, as well as the other nutrients (P≤0.05). The behavioral characteristics related to feed intake appear to be correlated, which allows for inferences through the study of these variables. The activities related to nutrient intake, with respect to time and efficiency, can be expressed directly through the animal behavior.